Raman spectroscopy of regulatory protein Omega from Streptococcus pyogenes plasmid pSM19035 and complexes with operator DNA. Issue 2 (2003) - Dostál Dostál, Lubomίr Lubomίr; Misselwitz Misselwitz, Rolf Rolf; Laettig Laettig, Stefan Stefan; Alonso Alonso, Juan C. Juan C.; Welfle Welfle, Heinz Heinz
Abstract : pSM19035-encoded homodimeric ω protein (ω2 ) regulates transcription of genes required for control of plasmid copy number and stable inheritance. ω2 belongs to the MetJ/Arc structural superfamily of repressors forming a ribbon-helix-helix (RHH) DNA binding motif, and binds specifically to operator regions containing at least two consecutive copies of heptad sequences 5 ' - A /T ATCAC A /T -3 ' in direct or inverted orientation. Solution properties of a double stranded 19 base-pairs oligonucleotide designed to model an operator DNA binding site of ω2 (top strand 5 ' -GCG AATCACA TGTGATT GG-3 ' ), ω2, and the ω2 :19-bp DNA complex were analysed by Raman spectroscopy. The Raman data indicate a sequence specific induced fit of both interacting macromolecules with ω2 binding to the major groove of the DNA, large perturbations of the DNA attributable to base unstacking, changes in vibrational modes of deoxyribose moieties, and protein-induced DNA bending. Protein marker bands indicate that α-helices are preserved, whereas amino acid side chains are largely perturbed, and unordered structures and turns become extensively restructured. Raman difference bands are consistent with interactions of thymine, adenine and cytosine with ω2 side chains. The results suggest that the central TCA/TGA stretch of the heptads might be the main target site for ω2 binding to operator DNA.